PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI WAKAF UANG - Indirwan Indirwan (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
The largest number of Muslims in the world, especially in Indonesia, is the biggest asset for the collection and development of money waqf. Money waqf management system is not much different from land or building waqf, Nazhir is tasked with investing according to sharia on one condition: the nominal value of the money invested cannot be reduced. While the investment return is allocated for Nazir (maximum 10%) and community welfare (minimum 90%). In the provisions of the law there are two models of money endowments, namely money endowments for a certain period of time and money waqf forever. A wakif can determine the type of earmarked property, for example, for integral community empowerment. Such as educational empowerment, empowerment, health empowerment, social empowerment and economic empowerment of a community. Such is the magnitude of the benefits of money waqf for community empowerment, it needs to be encouraged by public awareness to be able to participate actively in this money waqf movement. The potential for substantial funds from money waqf will be able to provide greater benefit for the development of the people and the welfare of the community.